2016
DOI: 10.1038/cdd.2016.97
|View full text |Cite|
|
Sign up to set email alerts
|

LH prevents cisplatin-induced apoptosis in oocytes and preserves female fertility in mouse

Abstract: Premature ovarian failure and female infertility are frequent side effects of anticancer therapies, owing to the extreme sensitivity of the ovarian reserve oocytes to the damaging effects of irradiation and chemotherapy on DNA. We report here a robust protective effect of luteinizing hormone (LH) on the primordial follicle pool of prepubertal ovaries against the cisplatin (Cs)-induced apoptosis. In vitro LH treatment of prepubertal ovarian fragments generated anti-apoptotic signals by a subset of ovarian somat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 61 publications
(60 reference statements)
6
86
0
1
Order By: Relevance
“…Some scholars found that sildenafil inhibited the loss of antral follicles induced by cisplatin and increased the level of AMH (Taskin, Yay, Adali, Balcioglu, & Inceboz, 2015). A study by Rossi et al (2017) has shown the rescue of the number of primordial follicles in prepubescent mice treated with luteinizing hormone, which increased the chance of pregnancy and number of offspring. Jang et al (2017) found that melatonin and ghrelin could promote the binding of Foxo3a to the p27Kip1 promoter to inhibit the phosphorylation of Foxo3a, thus reducing the activation of primordial follicles induced by cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars found that sildenafil inhibited the loss of antral follicles induced by cisplatin and increased the level of AMH (Taskin, Yay, Adali, Balcioglu, & Inceboz, 2015). A study by Rossi et al (2017) has shown the rescue of the number of primordial follicles in prepubescent mice treated with luteinizing hormone, which increased the chance of pregnancy and number of offspring. Jang et al (2017) found that melatonin and ghrelin could promote the binding of Foxo3a to the p27Kip1 promoter to inhibit the phosphorylation of Foxo3a, thus reducing the activation of primordial follicles induced by cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Eight-day-old (P8) female CD-1 mice were purchased from Charles River Laboratories. Ovaries were harvested, transferred to sterile 96-well plates with 50 µl α-MEM (+L-Glu, Gibco) supplemented with 10% FBS (Gibco), 1x penicillin/ streptomycin (Gibco), 0.2 mg/ml Na-pyruvate (Gibco), 2 mg/ml N -acetyl-l-cysteine (Sigma) and ITS liquid media supplement (100x) (Sigma) cultured at 37°C with 5% CO 2 overnight 32 . The final concentrations of the kinase inhibitors targeting ATM (KU55399, Selleckchem), CHK2 (BML-277, Merck) and CK1 (PF 670462, Sigma Aldrich) were 25 µM.…”
Section: Methodsmentioning
confidence: 99%
“…For each analysis of every experimental treatment, all technical replicates from one patient were combined to give a single datapoint. Tissues were exposed to chemotherapy drugs for a short time period, as in previous work by us and others, to mimic the short period of exposure that patients usually experience each drug cycle (Morgan et al 2013, Lopes et al 2014, Lande et al 2017, Rossi et al 2017, Smart et al 2018. On Day 3 of culture, after 24 h of drug exposure, tissue from experimental treatments was moved to drug-free medium for 96 h, with medium changed after 48 h: Control tissue was kept in drug-free medium throughout, with medium changed at the same time as for experimental groups.…”
Section: Human Ovary Tissue Culturementioning
confidence: 99%